Factors affecting radiographic progression of knee osteoarthritis. Issue 1 (January 1995) - Ledingham, J; Regan, M; Jones, A; Doherty, M
Abstract : OBJECTIVES--To evaluate the prognostic significance of patient characteristics and radiographic features at the knee for outcome of knee osteoarthritis. METHODS--This was a prospective observational study of 350 osteoarthritic knees. Clinical and radiographic data were obtained on 188 hospital referred patients (mean age 70, range 34-91 years). RESULTS--Median duration of follow up was two years (range 1-5 years). The majority of patients (48%) reported deterioration, but 23% experienced improvement in symptoms during the study period. Reported exercise tolerance remained unchanged in the majority (62%) and deteriorated in 35%. Change in at least one individual radiographic feature of osteoarthritis was seen in 252 (72%) knees: increase in joint space narrowing occurred in 52%, osteophyte in 32%, cysts in 19%, sclerosis in 14%, and attrition in 30%. Increase in Kellgren grade occurred in 137 (39%) knees. Knee effusion, osteoarthritis at multiple joint sites, and nodal change associated with change in Kellgren grade (odds ratios 1.03, 2.39, and 1.80; 95% confidence intervals (CI) 1.01 to 1.05, 1.16 to 4.93, and 1.02 to 3.17, respectively); warmth at the knee associated with change in any radiographic feature (odds ratio 2.22; 95% CI 1.19 to 4.14). Development of, or increase in, attrition and joint space narrowing associated with worsening symptoms and function and occurred with increased frequency in knees with effusions, clinical warmth and calcium pyrophosphate crystals in synovial fluid (p < 0.05). CONCLUSIONS--A high rate of change, radiographic more than clinical, was seen in osteoarthritic knees during this study. Poor clinical and radiographic outcome associated with calcium pyrophosphate crystal deposition and clinical inflammation as reflected by knee effusion and warmth.